Morphological characterization and quality assessment of cashew (Anacardium occidentale L.) nuts from 53 accessions of Burkina Faso - Judith Nomwendé Semporé; Laurencia Toulsoumdé Songré-Ouattara; Windpouiré Vianney Tarpaga; Fabrice Bationo; Mamoudou Hama Dicko (Journal of Agriculture and Food Research, 2021)
Cashew (Anacardium occidentale L.) is important in the world market, including Burkina Faso. This stimulated the implementation of a breeding program on species, targeting on high profitability cashew accessions of food-grade and economical interest. In the present study, nuts from a core of 53 cashew accessions from western Burkina Faso were physico-chemically characterized for the development of more profitable and competitive varieties on the international market. Morphological characteristics including length, width, thickness, weight, kernel yield and technological quality, mainly graining and kernel output ratio (KOR), respectively were evaluated by standard methods. Results showed that the nuts had a mean weight of 6.71 ± 1.13 g, with length, width and thickness of 3.15 ± 0.30 cm, 2.54 ± 0.22 cm, 1.75 ± 0.23 cm, respectively. Samples were mostly composed of large nuts with 86.79% of the nuts of the cashew accessions having a kernel weight below 180 nuts/kg. More than half of the nuts had a very good KOR above 50 lbs. Hierarchical ascending classification allowed to distinguish four groups of nuts which were differentiated by weight, graining, kernel yield and KOR. The graining results showed that 96.22% the nuts, were good quality. Among nuts, 23 out of 53 belonging to groups I, II and III are proposed to be used as seeds for obtaining potential variety for the cashew industry. They can also be candidates as mother trees for crossing to create efficient hybrid varieties that produce interesting medium weight nuts with high kernel yield, KOR and graining.